Efficacy of ondansetron against emesis induced by a multiple-day cisplatin-based chemotherapy regimen for malignant lymphoma. Issue 1 (1st January 2021) - Kamiya, Takahiro; Sakurai, Masatoshi; Kikuchi, Taku; Okayama, Mikio; Mizuno, Kota; Tanigawa, Tomohiko; Koda, Yuya; Kato, Jun; Mori, Takehiko
ABSTRACT: Objectives: This study aimed to evaluate the antiemetic efficacy of a 5-hydroxytryptamine-3 receptor antagonist (5-HT3RA), ondansetron, in patients with malignant lymphoma receiving multi-day cisplatin-based combination chemotherapy. Methods: We conducted a single-institution retrospective analysis of patients receiving the first course of an ESHAP (etoposide, cisplatin, methylprednisolone, cytarabine) regimen including 4-day continuous infusion of cisplatin (25 mg/m 2 /day). All patients received ondansetron 4 mg intravenously during 5-day administration of ESHAP. The primary endpoint was complete response (CR) for emesis, which was defined as absence of both emesis and rescue medications. Total control (TC) was defined as an absence of emetic episodes, including nausea and emesis, and complete protection (CP) was defined as an absence of emesis with addition of rescue antiemetics. Nausea and vomiting were assessed and graded daily by medical staff. Results: Eighty-two patients were analyzed. Nausea and vomiting were generally well controlled, with the CR rates of emesis being 79% in the overall phase, 82% in the early phase (days 1–6), and 89% in the delayed phase (days 7–10). TC and CP were achieved in 51 patients (62%) and 77 patients (94%) in the overall phase. Discussion: Most of the chemotherapy regimens for lymphoid malignancies include high-dose corticosteroid which may be also effective as antiemetics. Although NK1 receptor antagonist (NK1RA) is generally recommended for cisplatin-containing chemotherapy, it can interact with variety drugs. Conclusion: Although NK1RA is generally recommended for cisplatin-containing regimen, our results suggest that ondansetron effectively controlled emesis in patients receiving ESHAP therapy which includes high-dose corticosteroid.